Developing promiscuous glycosidases for glycoside synthesis: residues W433 and E432 in Sulfolobus solfataricus beta-glycosidase are important glucoside- and galactoside-specificity determinants. - Hancock, S; Corbett, K; Fordham-Skelton, A; Gatehouse, J; Davis, B (2005)
Two residues that have been implicated in determining the substrate specificity of the thermophilic beta-glycosidase from the archaeon Sulfolobus solfataricus (SsbetaG), a member of the glycosyl hydrolase family 1, have been mutated by site-directed mutagenesis so as to create more versatile catalysts for carbohydrate chemistry. The wild-type and mutated sequences were expressed in E. coli with a His(7)-tag to allow one-step chromatographic purification. The E432C and W433C mutations removed key interactions with the OH-4 and OH-3 of the sugar substrates, thus reducing the discrimination of glucose, galactose and fucose with respect to other glycosides. This resulted in two glycosidases with greatly broadened substrate specificities. Observed changes include a 24-fold increase in Man:Gal activity and an 18-fold increase in GalA:Gal activity. This promiscuous substrate tolerance was further illustrated by the parallel synthesis of a beta-glycoside library of glucose, galactose, xylose and mannose in one pot at 50 degrees C, in organic solvent. The synthetic potential of the catalysts was further evaluated through alkyl glycoside transglycosylation yields, including the first examples of synthesis of beta-mannosides and beta-xylosides with SsbetaG.